2021
DOI: 10.1080/1612197x.2021.1877326
|View full text |Cite
|
Sign up to set email alerts
|

Elite athletes’ achievement goals, burnout levels, psychosomatic stress symptoms, and coping strategies

Abstract: Elite athletes undergo intensive training and competitive pressure to succeed, making them susceptible to professional strain. However, they differ in their subjective reactions in the form of burnout levels and psychosomatic stress symptoms. Following a motivational perspective, these differences may be explained by the goals that athletes pursue. The current study therefore examined the effects of elite athletes' achievement goals on their burnout levels and psychosomatic stress symptoms, and to what extent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 94 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…These findings have evident implications for future emergency services personnel, but also for elite athletes. Research indicates that the careers of many successful athletes end prematurely due to psychological factors such as stress, low motivation, high anxiety, and self-confidence problems—all of which impact their resilience ( Hill et al, 2010 ; Bicalho and Costa, 2018 ; Aron et al, 2019 ; Ozdemir, 2019 ; Daumiller et al, 2021 ). Other research found that low emotional intelligence was related to anxiety and self-confidence issues ( Trigueros et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have evident implications for future emergency services personnel, but also for elite athletes. Research indicates that the careers of many successful athletes end prematurely due to psychological factors such as stress, low motivation, high anxiety, and self-confidence problems—all of which impact their resilience ( Hill et al, 2010 ; Bicalho and Costa, 2018 ; Aron et al, 2019 ; Ozdemir, 2019 ; Daumiller et al, 2021 ). Other research found that low emotional intelligence was related to anxiety and self-confidence issues ( Trigueros et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are notable similarities between emergency services personnel and elite athletes, where both occupations: (1) are performance-based; (2) experience high expectations, pressure, and stress; and (3) are required to have psychological resilience and effective coping mechanisms ( Bicalho and Costa, 2018 ; Doyle et al, 2021 ). Furthermore, research outlines that both occupations experience significant mental health concerns including depression, anxiety, burnout, and post-traumatic stress disorder (PTSD), and these conditions directly interfere with their ability to perform and execute their occupational responsibilities ( Rice et al, 2016 ; Regehr and LeBlanc, 2017 ; Shin and Kong, 2017 ; Klimley et al, 2018 ; Aron et al, 2019 ; Daumiller et al, 2021 ; Lynch, 2021 ). For these reasons, the following research: (1) explored the experiences of emergency services personnel; (2) characterised connections between emotional awareness and resilience; and (3) reflected on the ways these findings can be extrapolated to elite athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis should be on formulating individually relevant goals targeting controllable factors and considering goals as inherently flexible, to prevent frustration or similar issues that may arise from necessary, unexpected adjustments. Additionally, Daumiller et al [ 67 ] found that mastery approach goals were negatively associated with burnout levels and psychosomatic stress, whereas mastery avoidance goals were positively associated with burnout levels. This suggests that goals should be aimed at improving skills and knowledge rather than preventing their loss or stagnation.…”
Section: Diagnosis Of Stressmentioning
confidence: 99%
“…Elite athletes experience high levels of stress ( 16 ). Athletic environments are dynamic, and athletes' responses to changing stressors contribute to their adaptability and success in their respective sport.…”
Section: Literature Reviewmentioning
confidence: 99%